EVALUATION OF DRUG UTILIZATION IN HYPERTENSIVE PATIENTS WITH CHRONIC KIDNEY DISEASE AT IBNU SINA HOSPITAL - Firandi, Adelia; Norcahyanti, Ika; Irawanto, Dedi; Rachmawati, Ema; Kusumaningrum, Yunita Dyah (LPPM STIKES BULELENG, 2025)
Persistent and uncontrolled hypertension can cause damage to other organs, including the kidneys. In Indonesia, hypertension is the third leading cause of kidney disease, contributing 25.8% of all kidney disease. Hypertensive patients with chronic kidney failure generally receive different antihypertensive medications from one patient to another due to the individual use of medications and the varying effects of the drugs among individuals. Rational drug use is one of the important factors in providing healthcare services for patients according to the standards. The evaluation of drug utilization serves to make sure proper, safe, and effective use of medications. This study aims to determine the patient demographics, regimen of the medicines, and the incidence of Drug Related Problem (DRP) in hypertensive patients with chronic kidney disease at RSUD Ibnu Sina from January to June 2021. This study is an observational research using a descriptive method. Data was collected from a retrospective analysis of patient medical records, and 18 patients who met the inclusion criteria were identified. The most commonly used is single antihypertensive medications (38.9%) from the diuretic group (furosemide) and the ARB group (candesartan and losartan). In the profile of additional medications, vitamins and minerals (88.9%), gastric ulcer prophylactics (66.7%), and antiemetics (61.1%) were found. DRP (P1.2) (50%) was caused by several factors, namely (C3.3) (25%), (C3.2) (15%), (C3.1) (5%), and (C4.1) (5%).